Proceedings of the 3rd ACM SIGSPATIAL International Workshop on AI for Geographic Knowledge Discovery 2019
DOI: 10.1145/3356471.3365236
|View full text |Cite
|
Sign up to set email alerts
|

Kartta Labs

Abstract: This paper introduces the Kartta Labs project, an ongoing opensource and open-data project aiming at organizing the world's historical maps and making them universally accessible and useful. Kartta Labs' framework is designed as a composition of multiple modules. Each module has a crowdsourcing implementation and an artificial intelligence based implementation. The framework takes images of historical maps, registers them in space and time, generates a vector version of the map content, and allows the users to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, the map interpretation is still a difficult task. In recent years, the focus of map interpretation has primarily been on georectification to historical maps (Tavakkol et al, 2019), as well as recognizing specific map features (Chiang et al, 2020) and their semantic information (Wang et al, 2023). Gui et al (2023) suggested that users' intention of map image retrieval can be analyzed from a three-tiered structure of "intention, sub-intention, dimension component", and constructed a map retrieval intention dimension tree.…”
Section: Semantic Retrieval Of Map Imagesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the map interpretation is still a difficult task. In recent years, the focus of map interpretation has primarily been on georectification to historical maps (Tavakkol et al, 2019), as well as recognizing specific map features (Chiang et al, 2020) and their semantic information (Wang et al, 2023). Gui et al (2023) suggested that users' intention of map image retrieval can be analyzed from a three-tiered structure of "intention, sub-intention, dimension component", and constructed a map retrieval intention dimension tree.…”
Section: Semantic Retrieval Of Map Imagesmentioning
confidence: 99%
“…However, the map interpretation is still a difficult task. In recent years, the focus of map interpretation has primarily been on georectification to historical maps (Tavakkol et al., 2019), as well as recognizing specific map features (Chiang et al., 2020) and their semantic information (Wang et al., 2023). Gui et al.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations